Pengaruh Pelajaran Nilai-Nilai Kemanusiaan, Meditasi, Praktik Berkesadaran dan Genta Penenang Terhadap Pembentukan Karakter Siswa SMA Nanyang Zhi Hui Medan - Taslim, Fanny; Ariawan, I Putu Wisna; Sunu, I Gusti Ketut Arya (Pascasarjana Universitas Pendidikan Ganesha, 2023)
This study aims to determine the effect of several variables, namely: (1) Human Values ​​lessons, (2) meditation, (3) mindfulness practices (4) calming bells together on the character building of Nanyang Zhi Hui High School students in Medan. The population in this study were 182 students of Nanyang Zhi Hui High School. Determination of the sample in this study using Inferential Statistics technique, which took a sample of SMA Nanyang Zhi Hui Medan. The data in this study were collected using a questionnaire component of the context of the Lesson of Human Values, meditation, mindfulness practices, calming bells and character. Data were analyzed using multiple regression analysis. The results showed that: (1) there was a significant influence of human values ​​on the formation of student character with an effect of 25.06%, (2) there was a significant effect of meditation on the formation of student character with an effect of 2.63%, (3) there is a significant effect of mindfulness practice on the formation of student character with an effect of 14.71%, (4) there is a significant effect of the calming bell on the formation of student character with an effect of 6.01%, and (5) together, there is significant influence of human values, meditation, mindful practices, and calming bells on the formation of student character with an effect of 48.4%.